The Influence of Work Motivation on Employee Performance at PT. Ramayana Lestari Sentosa TBK Samarinda Central Plaza Branch - Fenni Lala Permatasari Kuswanto; Sofia Ulfa Eka Hadiyanti; Askiah Askiah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of work motivation on employee performance at PT. Ramayana Lestari Sentosa Tbk Samarinda Central Plaza Branch, a national retail company that serves the community and operates in various regions of Indonesia. The main issue raised in this study is the extent to which work motivation affects employee performance amid operational challenges and work dynamics. To address this issue, this study employs a quantitative approach using a survey method, involving 127 respondents as a sample through an online questionnaire. The analytical techniques used include simple linear regression tests and partial tests (t-tests). The results of the study indicate that work motivation has a positive and significant impact on employee performance, suggesting that the higher the work motivation, the better the employee performance. These findings reinforce previous theories and underscore the importance of managing work motivation in supporting organizational productivity and success. The conclusion of this study is that enhancing work motivation can directly drive more optimal employee performance, so company management must continue to pay attention to motivational factors, both intrinsic and extrinsic.